Maternal and fetal outcome among pregnant women following open heart surgery (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
The aim of this retrospective cohort study was to evaluate the pregnancy outcome following open heart surgery for three years. Group I (n = 37) included pregnancy with history of intracardiac repair except valvular heart disease, while Group II (n = 19) included pregnancy with prosthetic valve received anticoagulation therapy. In total, 78.6% pregnancies ended in healthy live births, and 19.6% pregnancies terminated in abortion (8.1% patients in Group I and 42.1% patients in Group II). 5.3% baby was born with congenital malformation in Group II. Mean birth weight was found 2.8 ± 0.6 kg in Group I and 2.5 ± 0.3 kg in Group II. The mean APGAR score was found 8.5 ± 0.7 in Group I and 8.1 ± 0.7 in Group II. 19.6% patients developed cardiac complications during the pregnancy. Majority of the patients (89.2% in Group I and 63.2% in Group II) was found good health status. Proper antenatal care and early risk stratification are the fundamental measures to improve the maternal and fetal outcome in a patient of open heart surgery.